2005
DOI: 10.1016/j.femsec.2005.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of bacterial diversity along the human intestinal tract by direct cloning and sequencing of 16S rRNA genes

Abstract: Bacterial diversity of the mucosal biopsies from human jejunum, distal ileum, ascending colon and rectum were compared by analysis of PCR-amplified 16S rDNA clone libraries. A total of 347 clones from the mucosal biopsies were partially sequenced and assigned to six phylogenetic phyla of the domain Bacteria: Firmicutes, Bacteroidetes, Proteobacteria, Fusobacteria, Verrucomicrobia, and Actinobacteria. The jejunum sample had least microbial diversity compared to the other samples and a trend towards highest dive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
259
3
7

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 313 publications
(286 citation statements)
references
References 50 publications
14
259
3
7
Order By: Relevance
“…By contrast, Bacteroides sp. are among the most predominant genera of intestinal microbiota (Hold et al, 2002) and have been found to be dominant among bacteria on the ileal mucosal surface (Wang et al, 2005) and in accordance with the hypothesis of invasion of microorganisms through an ascending infection by duodenal biliary reflux (Sung et al, 1992) were observed in a high number (approximately 20%) of stent communities. This also explains the high prevalence in stent communities of acid-tolerant Streptococcus spp.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…By contrast, Bacteroides sp. are among the most predominant genera of intestinal microbiota (Hold et al, 2002) and have been found to be dominant among bacteria on the ileal mucosal surface (Wang et al, 2005) and in accordance with the hypothesis of invasion of microorganisms through an ascending infection by duodenal biliary reflux (Sung et al, 1992) were observed in a high number (approximately 20%) of stent communities. This also explains the high prevalence in stent communities of acid-tolerant Streptococcus spp.…”
Section: Discussionsupporting
confidence: 72%
“…This also explains the high prevalence in stent communities of acid-tolerant Streptococcus spp. and Lactobacillus spp., which were reported to be highly abundant in the ileum (Hayashi et al, 2005;Wang et al, 2005) and probably are major colonizers of the duodenum (Wilson, 2005). The immense prevalence of Veillonella sp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier investigations have not rigorously addressed possible differences in the intestinal bifidobacteria between individuals (Eckburg et al, 2005;Wang et al, 2005). We applied techniques that are based on the relative abundance of sequences within communities and the extent of genetic divergence between sequences.…”
Section: Analysis Of the Inter-participant Variabilitymentioning
confidence: 99%
“…Advances in microbial ecology including metagenomic studies of environmental samples have allowed microbial ecologists to access earlier unimaginable genetic diversity. Recently, metagenomic and microbiomic studies based on the analysis of genomic DNA-and rRNA gene libraries have highlighted the diversity of the GIT microbiota and have shown that it consists of many novel and, as yet, unculturable bacterial components (Eckburg et al, 2005;Wang et al, 2005;Gill et al, 2006;Kurokawa et al, 2007;Palmer et al, 2007). However, relatively few bifidobacterial rRNA gene sequences have so far been identified in these metagenomic studies, which are in striking contrast to what was described earlier in several bifidobacterial surveys, which had adopted culture-dependent approaches (Poxton et al, 1997;Harmsen et al, 2000;Fanaro et al, 2003).…”
mentioning
confidence: 94%